Role of forage legumes and constraints for forage legume seed production in Mediterranean Europe - Porqueddu C.; Ledda L.; Roggero P.P. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
This paper briefly describes the role of pasture and forage legumes in the farming systems of Mediterranean Europe. The present situation of the annual and perennial forage legume seed market is analysed. The major constraints for forage legume seed production in southern Europe are discussed and possible solutions to face the low level of seed production of well-adapted Mediterranean varieties are proposed. The future perspectives of forage legumes uses and their seed production in relationship to the need for economic and environmental sustainability are also reported.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)